MACROECONOMIC UNCERTAINTY AND GREEN STOCK MARKET ON ECONOMIC GROWTH IN INDONESIA - Arsyaf Tampubolon; Eka Martyna Theodora; Anggiat Sinaga; Dwita Sakuntala (SEAN Institute, 2023)
This study was conducted to be able to analyze factors that can affect economic growth in Indonesia. The dependent variable used in this study is economic growth and the dependent variables are BI policy rates, FED policy rates, world oil, exchange rates and green stock markets. The research was conducted in Indonesia with the data taken is the period from 2010 to 2022. The data source used is secondary data by taking data from the Indonesian Central Bureau of Statistics, and Bank Indonesia. Data analysis uses the help of e-views software by conducting multiple regression analysis tests. The results of this study apparently prove that the variables of BI policy rates, FED policy rates and exchange rates affect economic growth in Indonesia, while world oil, and the green stock market have no effect on economic growth in Indonesia.